Environmental Impact Assessment of An Urban Port: Noise Pollution Survey in the Port Area of Napoli (S Italy) - Casazza, Marco; Boggia, Francesca; Serafino, Gianmarco; Severino, Vincenzo; Lega, Massimiliano (Journal of Environmental Accounting and Management, 2026)
The quality of life, particularly in the urban environment, becomes degraded, due to a cumulative effect of multiple exposition to pollutants. A special case is represented by urban ports, due to the fact that multiple impacts are superimposed. Moreover, being the port connected to the surrounding urban context, the potential negative impacts are magnified by the high number of exposed citizens in the close vicinity. This is why appropriate monitoring actions constitute the basis to define strategic planning options toward a more livable environment in of port cities. Considering the specific case of noise pollution, due to the cost of monitoring tools, it is important to develop scientifically-sound methodological options to perform preliminary surveys, using available low-cost technologies. This choice has the purpose of minimizing the costs of monitoring, while maximizing its effectiveness. Considering the specific case study of the port area of Napoli (S Italy), this work refers to the use of a freeware, which can be downloaded and installed in a smartphone, with the purpose of performing geo-localized noise pollution surveys. In particular, after defining the quality of collected data through a preliminary laboratory inter-calibration, a series of field surveys were performed in 12 different points and measures were analyzed. Sound Pressure Level measures, which were found to be of higher quality, allowed to define two areas having different noise characteristics. Consequently, these areas could be disentangled in future monitoring operations, reducing the points of measure from 12 to 2. The obtained results suggest an option, which could be applied to other environmental parameters. Moreover, the quality of surveys could be further implemented through the use of aerial platforms, in order to obtain future 3D enhanced environmental scenarios assessment.